Surface Stability of Azobenzene‐Based Thin Films in Aqueous Environment: Light‐Controllable Underwater Blistering. Issue 9 (2nd February 2022) - Audia, Biagio; Fedele, Chiara; Tone, Caterina M.; Cipparrone, Gabriella; Priimagi, Arri
Abstract: Azobenzene‐based light‐responsive thin films are emerging as appealing candidates for smart cell‐culture substrates. Their attraction lies in the fact that they can be reversibly photo‐patterned, providing a route for dynamically mimicking the remodeling of the extracellular matrix. However, since the cells need to be cultured in aqueous environment, a key parameter in the layout of any biological application is the stability of the surface underwater. In this work, the authors perform a detailed investigation on the surface stability of azobenzene‐based thin films in water and in a biologically relevant aqueous medium in which surface blistering occurs, as a result of water–material interaction. The phenomenon arises due to film delamination, and it can be prevented by changing the underlying substrate, by an additional coating layer, or by photo‐induced control over the film permeability. It is also shown that the blister orientation can be controlled with polarized light. Furthermore, a simple model based on osmotic pressure is proposed to explain the blister formation. These findings provide a comprehensive overview of the interaction between water and the photo‐responsive film surface, pertinent for engineering biomaterials with enhanced dynamic control over the cell–material interface. Abstract : The morphological stability of azobenzene‐based film surface is tested in different aqueous environments and a water‐induced blistering instability is revealed. A blisters formation mechanism derived by the experimental observation is proposed. Additionally, simple routes for preventing the phenomenon are indicated, and photocontrol over the blister orientation and onset demonstrated.